Color-tunable transparent photovoltaics for onsite power production under sunlight and indoor light. (January 2023) - Kim, Sangho; Patel, Malkeshkumar; Youn, Sung-Min; Kim, Youngkuk; Lee, Kibum; Kim, Joondong
Abstract: Transparent photovoltaics (TPVs) are energy-generating devices made of transparent material and incorporating solar cell technology. The ultimate goal of using such devices is to reach a level of sustainability by harnessing energy from common structures such as windows on buildings and vehicles. Applications of this concept can be widened by incorporating a color-tuning scheme into TPVs. In this sense, light can be managed; here, we introduce a method for this using a ZnO-based back reflection method. Large-scale (16 cm 2 ) TPVs are achieved by solid-state sputtering of metal oxide layers. They exhibited high power conversion efficiency ( η ) (3.8% for indoor light-emitting diode lamp) and long-term stability (>100 days). The abrupt heterojunction between n-type ZnO and p-type NiO spontaneously forms a space charge region with a strong electric field. An additional thin Si film in the heterojunction effectively improves solar cell performance, making it useful for power generation, even under indoor illumination. Substantial efficiency of 3.02% was achieved by an Al-doped ZnO for the Sun spectrum. This implies the ability to produce TPV power from the Sun or artificial light in versatile ways. TPVs and color-tuned photovoltaics can be used in windows and other such objects to realize an onsite power supply. Graphical abstract: Image 1 Highlights: Large-scale transparent photovoltaic (TPV) enable onsite power of 7 W/m 2 via window. ZnO back reflector provides a color-tunable device for onsite power production. TPV has an efficiency of 0.68% and 3.8% under solar spectrum (AM1.5G) and indoor light. TPV under the sunlight-powered electric fan with stability and see-through feature. Colorful TPV implies onsite power from Sun and artificial light in a versatile way.